Manifolds III Developments and Developments and Applications - Bracken, Paul (IntechOpen, 2022)
The subject of manifolds is an exciting area of research in modern mathematics. This volume presents five chapters that discuss manifolds and some of their applications to other areas of study. It is designed to provide researchers further insight into what is current in the field and will hopefully spur further study.